FACTORS INFLUENCING THE INCREASE IN THE LEVEL OF COMPETITIVENESS OF THE TEXTILE INDUSTRY ENTERPRISE (World Economics and Finance Bulletin, 2023)
For the sustainable development of enterprises of any type, it is necessary to know the factors that affect its competitiveness. It is on this aspect that the future of a particular enterprise depends. Brand creation, staff training and many other factors that in one way or another contribute to the sale of goods are direct indicators of competitiveness. Competition stimulates development in all areas and directions, which has a positive effect on consumer satisfaction.
Keywords: textile industry; brand creation; innovation